Farmers’ Awareness Level towards Solar Energy Products - Kaur, Hansdeep; Sandhu, Vikram (International Journal of Psychosocial Rehabilitation, 2020)
The solar system opportunities are significant in India and have a potential of replacing huge usage of diesel and kerosene used for lighting and irrigation in rural areas. As a result, Indian government is providing various financial supports and subsidies to buy solar energy products. But still, the demand for these products is not favourable by public. In this aspect, it becomes necessary to find out why people are not buying solar energy products and whether they are willing to buy solar energy products. Therefore, the present study is an attempt to examine the farmers' awareness levels towards solar energy products. To accomplish the objective, respondents were interviewed in three major regions Malwa, Majha, and Doaba of Punjab. Respondents’ data was collected through convenience as well as judgmental sampling. The data has been collected during the period of May 2015 to May 2017. Descriptive analysis and Chi-square (χ2) techniques have been used to examine the collected data. A result of the study concluded that most of the respondents were aware of solar energy products, and they got awareness from their friends and family. But they are not adopting solar products due to its high investment cost and government grant aid available is inadequate for buying solar energy products.